2023
DOI: 10.3390/cells12091344
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polo-Like Kinase 1 in Regulating the Forkhead Box Family Transcription Factors

Abstract: Polo-like kinase 1 (PLK1) is a serine/threonine kinase with more than 600 phosphorylation substrates through which it regulates many biological processes, including mitosis, apoptosis, metabolism, RNA processing, vesicle transport, and G2 DNA-damage checkpoint recovery, among others. Among the many PLK1 targets are members of the FOX family of transcription factors (FOX TFs), including FOXM1, FOXO1, FOXO3, and FOXK1. FOXM1 and FOXK1 have critical oncogenic roles in cancer through their antagonism of apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 201 publications
0
0
0
Order By: Relevance
“…PLK1 is high-expressed in various cancers and is related to unfavorable prognosis ( Galusic et al, 2020 ). Increasing evidence suggested that PLK1 regulates several critical TFs in cancers and facilitates cell proliferation, metastasis, epithelial mesenchymal transition ( Moore, Gheghiani & Fu, 2023 ; Iliaki, Beyaert & Afonina, 2021 ). These findings indicated that PLK1 may be a promising target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 is high-expressed in various cancers and is related to unfavorable prognosis ( Galusic et al, 2020 ). Increasing evidence suggested that PLK1 regulates several critical TFs in cancers and facilitates cell proliferation, metastasis, epithelial mesenchymal transition ( Moore, Gheghiani & Fu, 2023 ; Iliaki, Beyaert & Afonina, 2021 ). These findings indicated that PLK1 may be a promising target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%